A glimpse of Malaysian teachers' reading intervention strategies for children with Dyslexia / Aznoora Osman, Wan Ahmad Jaafar Wan Yahaya and Aznan Che Ahmad - Osman, Aznoora; Wan Yahaya, Wan Ahmad Jaafar; Che Ahmad, Aznan (UiTM Cawangan Perlis, 2016)
This paper explores contemporary issues surrounding the teaching of reading towards dyslexic children in Malaysia. The objectives of the literature review and preliminary investigation were to ascertain the complexity of the issues, and to make informed decisions that warrant the development of educational app targeted for educators. It was discovered that children with dyslexia would normally experience distinctive learning difficulties than other children of learning disabilities. Nevertheless, the study revealed that most of them did not receive suitable classroom intervention. When teaching reading to these children, teachers should be aware of the major causes of their reading difficulties, and then employs strategies that could accommodate their personal strengths and weaknesses. Dyslexic children are often stigmatised and isolated by teachers and friends; therefore, it is vital to provide equal opportunity to learn for them. The result of this study calls for serious deliberation to train teachers about effective literacy intervention techniques that are precisely tailored for children with dyslexia.